2006
DOI: 10.1016/j.edurev.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Working memory, fluid intelligence, and science learning

Abstract: A review of the history of working memory (WM) studies finds that the concept of WM evolved from short-term memory to a multi-component system. Comparison between contemporary WM models reveals: (1) consensus that the content of WM includes not only task-relevant information, but also task-irrelevant information; (2) consensus that WM consists of phonological and visuospatial components; (3) consensus that short-term memory storage is a function of WM; (4) disagreement as to whether an independent executive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 61 publications
3
75
0
5
Order By: Relevance
“…It is clear from many studies that next to intra-individual differences in working memory capacity (see e.g., Sandberg et al 1996) there are also inter-individual differences in working memory capacity (see e.g., Miyake 2001). Different tests for measuring working memory capacity exist (for an overview see, Yuan et al 2006). The most well known of these tasks is the operation span task (OSPAN) introduced by Turner and Engle (1989); different operationalizations of this test exist (see e.g., PardoVazquez and Fernandez-Rey 2008).…”
Section: Individual Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear from many studies that next to intra-individual differences in working memory capacity (see e.g., Sandberg et al 1996) there are also inter-individual differences in working memory capacity (see e.g., Miyake 2001). Different tests for measuring working memory capacity exist (for an overview see, Yuan et al 2006). The most well known of these tasks is the operation span task (OSPAN) introduced by Turner and Engle (1989); different operationalizations of this test exist (see e.g., PardoVazquez and Fernandez-Rey 2008).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Box 217, 7500 AE Enschede, The Netherlands e-mail: a.j.m.dejong@utwente.nl working memory capacity for cognitive functioning is evident. A series of studies have found that individual working memory performance correlates with cognitive abilities and academic achievement (for an overview see Yuan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(Matson, 2005). As competências auditivas apresentam, pois, um papel crucial no desenvolvimento das representações de tipo fonológico, sendo a memória auditiva de particular relevância l tanto para a aquisição linguística como para a realização de diferentes aprendizagens de âmbito escolar (Gathercole, 1998, Yuan, Shavelson, Alonzo & Oppezzo, 2006. Quando existem dificuldades a nível do processamento auditivo, poderão ocorrer representações fonológicas menos precisas o que terá implicações a nível da fala e futuramente da ortografia (Snowling & Stackhouse, 2004).…”
Section: Introductionunclassified
“…Uma criança que manifesta dificuldades ao nível da memória auditiva pode ser incapaz de recordar os fonemas, pode incorrer em processos fonológicos de variada natureza, apresentar dificuldades em memorizar sequências ou alterar os sons que constituem uma determinada palavra (Capovilla & Capovilla, 2003). Deste modo, uma perturbação ou alteração no processamento auditivo pode afetar diferentes dimensões da linguagem materializando atrasos ou perturbações no desenvolvimento linguístico (Shavelson, Alonzo & Oppezzo, 2006). O Atraso de Desenvolvimento de Linguagem (ADL) engloba os atrasos na aquisição e/ou desenvolvimento da linguagem, sem que a tais limitações estejam associados a uma causa orgânica, clinicamente determinada e onde o quadro linguístico presente se manifesta com particular evidência nos distintos processos fonológicos de simplificação.…”
Section: Introductionunclassified
“…This distinction, however, is crucial to understanding how the human memory acquires information (Bargh & Chartrand, 1999;Bargh & Ferguson, 2000), and how students can apply the acquired information to comprehending their environment. The most common consensus on these questions is that external information enters into short-term memory (STM) and long-term memory (LTM) through the sensory systems (Yuan, Steedle, Shavelson, Alonzo, & Oppezzo, 2006). STM is the transitory storage of data, in which the working memory manipulates and stores limited information temporarily (Anderson, 2005).…”
Section: Conscious and Unconscious Information Processing In Human Mementioning
confidence: 99%